Upper Cretaceous Nannofossils Biostratigraphy from Cyrenaica, NE Libya. - El-Mehaghag, Ali; Muftah, Ahmed; Alshahomi, Khalifa (Libyan Journal of Science &Technology, 2022)
The Upper Cretaceous succession of the Well E1-NC152 in the Soluq Depression area of Cyre-naica region in Northeastern Libya, as well as the surface exposure of the Qasr al Abid For-mation in Jardas al Abid area of Cyrenaica, have been biostratigraphically analyzed. The stud-ied section of well E1-NC152 is assigned to the early Cretaceous (late Albian) – late Cretaceous (early Campanian) of Nannofossil Biozones (CC9 to CC22) of Sissingh (1977) and Perch-Niel-sen (1985) which is respectively corresponding to UC5 to UC14 Biozones of Burnett (1998). These biozones are Calculites ovalis (CC19) – Quadrum trifidum (CC22) (early-late Campa-nian); Calculites obscurus Biozone (CC17) – Aspidolithus parcus gr. parcus Biozone (CC18) Late (Santonian– Early Campanian); Reinhardtites anthophorus Biozone (CC15) - Lucianorhabdus cayeuxii (CC16) (Santonian according to Sissingh (1977); Lucianorhabdus maleformis Biozone (CC12) - Micula decussata Biozone (CC14) (middle Turonian – middle Coniacian); Eiffellithus turriseiffilii Biozone (CC9) – Microrhabdulus decorates Biozone (CC10a) (late Albian – Cenoma-nian). However, the upper Cenomanian Qasr al Abid Formation at the outcrop is assigned to CC10a of Sissingh (1977) and Perch-Nielsen (1985) which is corresponding to UC3 (a-d) of Burnett (1998). Furthermore, correlation attempts with other published studies in the region have been performed to tie surface with the subsurface calcareous nannofossils distribution.